Implementation of Educational Innovations in Student Management, Facilities, Curriculum, and Public Relations in Integrated Science-Social Studies Learning at MI Al-Islamiyah Bangil: A Case Study - Firdausi Nurharini; Siti Eneng Sururiyatul Muaziyah; Nabila Shidqiyyah (Equator Science Journal, 2024)
Education in Madrasah Ibtidaiyah plays a crucial role in shaping students' character and competencies. This study aims to identify and analyze educational innovations implemented at MI Al-Islamiyah Bangil, focusing on student achievement, literacy, character development, facilities, curriculum, and community engagement. A qualitative descriptive method was employed to gain in-depth understanding through interviews with the Vice Principal. The findings reveal that MI Al-Islamiyah actively implements various innovations, such as tailoring teaching approaches to students' learning styles, establishing reading corners to enhance literacy, and fostering strong community relationships through parent-teacher associations. Despite limitations in facilities, the school strives to improve overall educational quality. This study is expected to serve as a reference for developing educational innovations in other institutions.